Comparative Evaluation of Animated Distraction Versus Virtual Reality During Local Anaesthetic Injection in Children (Academia Journal of Medicine, 2026)
Background: Pain and anxiety during local anaesthetic administration remain major  concerns in pediatric dental patients. Various distraction techniques have been introduced to  improve child cooperation and reduce fear during dental procedures. Animated distraction  and virtual reality are commonly used non-pharmacological behaviour management  techniques in Pediatric Dentistry. Aim: To comparatively evaluate the effectiveness of animated distraction and virtual reality  distraction during intraoral local anaesthetic injection in children. Materials and Methods: The present randomized controlled clinical trial was conducted on  30 children aged 5–10 years requiring local anaesthetic administration for dental treatment.  Participants were randomly divided into two groups of 15 each. Group I received animated  distraction using age-appropriate cartoons displayed on a mobile device, while Group II  received virtual reality distraction using a VR headset with child-friendly audiovisual content  during injection administration. Topical anaesthetic gel was applied prior to injection in  both groups. Pain perception was assessed using the Wong–Baker Faces Pain Rating Scale,  anxiety was evaluated using pulse rate and Facial Image Scale, and behaviour was assessed  using Frankl Behaviour Rating Scale. The obtained data were statistically analyzed using  independent t-test and Chi-square test with significance level set at p < 0.05. Results: Children in the virtual reality group demonstrated lower pain and anxiety scores  compared to the animated distraction group. Pulse rate increase during injection was also  lower in the virtual reality group. Improved behaviour ratings and better cooperation were  observed among children receiving virtual reality distraction. However, the difference  between the groups was statistically significant for pain perception and anxiety scores. Conclusion: Both animated distraction and virtual reality distraction were effective in  reducing pain and anxiety during local anaesthetic administration in children. However,  virtual reality distraction showed superior effectiveness and improved child cooperation  during dental procedures.
Keywords: Virtual reality, Animated distraction, Local anaesthetic injection